5(.5-3)+3(.5+3)=2(.5)-3

Simple and best practice solution for 5(.5-3)+3(.5+3)=2(.5)-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(.5-3)+3(.5+3)=2(.5)-3 equation:


Simplifying
5(0.5 + -3) + 3(0.5 + 3) = 2(0.5) + -3

Combine like terms: 0.5 + -3 = -2.5
5(-2.5) + 3(0.5 + 3) = 2(0.5) + -3

Multiply 5 * -2.5
-12.5 + 3(0.5 + 3) = 2(0.5) + -3

Combine like terms: 0.5 + 3 = 3.5
-12.5 + 3(3.5) = 2(0.5) + -3

Multiply 3 * 3.5
-12.5 + 10.5 = 2(0.5) + -3

Combine like terms: -12.5 + 10.5 = -2
-2 = 2(0.5) + -3

Multiply 2 * 0.5
-2 = 1 + -3

Combine like terms: 1 + -3 = -2
-2 = -2

Add '2' to each side of the equation.
-2 + 2 = -2 + 2

Combine like terms: -2 + 2 = 0
0 = -2 + 2

Combine like terms: -2 + 2 = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 8u^2-9u-3=0 | | 3x^3+33x^2+90x= | | 2m^2+4m+2=0 | | 3x^3+6x=4x^2+8 | | x+2x+2= | | 6(1x-1x)=11x-2(x+2) | | 7.2-3y=5 | | 5r-5r=1 | | 7.1-3y=5 | | 5.2+y=10 | | 3x+2x-20+4x-20=180 | | 5.1+y=10 | | -49x^2+6=-7x | | 5v-2v=-24 | | -4-n-4n+15=0 | | 9y+9-9y=18-9y | | 5x^2-110x+105= | | -5x+15=7x-21 | | 7-3y=5 | | 1/2(10-2)-1/6(60-5) | | 0.5x+0.83=0.66x-0.25 | | -5(x-3)=7(x-3) | | 22p+2p+p= | | 160=x+(4x+10) | | 3x+4(600-x)=2200 | | 3w-5=2(w+8)+w | | 3x+6=2x+8whatisx | | c(3)+c+25+c=180 | | 3w-5=2(w+13)+w | | -3y^2-9y+4x-12=0 | | -5+3x=20 | | 3-8x-2=1 |

Equations solver categories